Effect of Transformational and Transactional leadership Style on Employees’ Performance in Lebanese Universities - Ezzeddine, Ali Hassan (REVENUE: Jurnal Manajemen Bisnis Islam, 2023)
The effectiveness of individual employee’ performance depends on the leader/supervisor. Effective leader can enhance the individual employee performance through proper leadership style and retain high performance and talent employees within the company. The behavior of leader is very importance to improve job performance and retain skillful employees for longer period in the organization. This study aims to investigate the effect of transformational leadership and transactional leadership styles on employees’ performance in Lebanese Universities. Three main variables consist in conceptual framework. They are independent variables (transformational leadership style, transactional leadership style and dependent variable (employee performance).  A sample of 400 respondents has been randomly selected from top four universities in Lebanon. Sample was selected by using simple random method and primary data was collected through structured questionnaires. Data analysis was conducted by using Statistical Package for Social Sciences (SPSS 23.0) and Smart-PLS 3.0. Results showed that both transformational leadership and transactional leadership styles have the significant effect on employees, performance in Lebanese universities. The outcomes of this study offered substantial empirical support to the research framework from a theoretical and managerial perspective.